Аналіз продуктивності системи виявлення дронів на основі IoT-мереж - Переметчик, Д. О.; Мартинчук, О. О. (ХНУРЕ, 2025)
Research has been conducted on next-generation IoT-based drone detection technology. Such a system provides improved performance parameters through flexibility, additional capabilities, and lower ongoing costs. To maximize the benefits for security operations, there is a software solution that is reliable and safe to implement with a full set of integrated features: efficient data analysis algorithms, adaptive sensor control, and machine learning to improve detection accuracy, without getting bogged down in problems of excessive power consumption or a high number of false positives.
Keywords: виявлення дронів; IoT-мережа